High temperature flexural strength of B4C–ZrB2 ceramic at 1000–1600 °C in air. Issue 10 (December 2015) - Cheng, Xiangmeng; He, Rujie; Qu, Zhaoliang; Ai, Shigang; Fang, Daining
Abstract: B4 C-30 vol% ZrB2 ceramic was prepared using hot pressing. The room temperature and high temperature flexural strength of the as-prepared ceramic were investigated. The room temperature flexural strength was measured to be 604.5 MPa. When the ceramic was tested at 1000 °C, the flexural strength kept nearly the same as room temperature flexural strength, because no serious oxidation happens and the oxide product can heal the cracks on the surface. When the temperature was above 1000 °C, oxidation becomes severer and the mechanical properties decrease sharply. The flexural strength at 1200, 1400 and 1600 °C is 451.5, 287.5 and 202.5 MPa, respectively. Microstructure evolution of the B4 C–ZrB2 ceramic was also investigated.